Pengembangan Konsep Desain Identitas Visual Melalui Penggunaan Supergrafis Pada Media Sosial Diskominfo (International Forum of Researchers and Lecturers, 2024)
In this digital era, social media has become an important communication channel for brands, institutions and agencies. Visual Identity Design is important in a brand. Apart from a brand, a visual identity is also needed for an official institution or agency. The function of visual identity design is as a sign of ownership, a means of identity, a promotional tool, a characteristic, and as a sign of the integrity of a brand or agency. The Communication and Informatics Service is an agency that is overseen by a government agency. This agency should build an identity with the aim of having more integrity, consistency and professionalism in the eyes of the public. Application of supergraphics, namely graphic elements that creatively combine visual elements with the aim of giving a strong impression, attracting attention and building a professional image of the Diskominfo agency from other agencies.